And the dish ran away with the spoon - Stevens, Janet; Crummel, Susan Stevens (San Diego : Harcourt, 2001)
When Dish and Spoon run away, their nursery rhyme friends Cat, Cow, and Dog set out to rescue them in time for the next evening$1 (Bs reading of their rhyme.s
Keywords: Characters in literature -- Fiction; Nursery rhymes -- Fiction